Arsenic Speciation and Metallomics Profiling of Human Toenails as a Biomarker to Assess Prostate Cancer Cases: Atlantic PATH Cohort Study - Erin Keltie; Erin Keltie; Kalli M. Hood; Kalli M. Hood; Yunsong Cui; Ellen Sweeney; Gabriela Ilie; Anil Adisesh; Anil Adisesh; Trevor Dummer; Veni Bharti; Veni Bharti; et al. (Frontiers Media S.A., 2022)
Chronic exposure to inorganic arsenic and trace metals has been linked to prostate cancer, and altered arsenic methylation capacity may have an important role in arsenic carcinogenesis. Biomarkers may be able to elucidate this role. Our objectives were to characterize profiles of arsenic species and metallome in toenails and urine samples, compare profiles between prostate cancer cases and controls, and determine the discriminant ability of toenail and urine biomarkers. Toenail samples (n = 576), urine samples (n = 152), and questionnaire data were sourced from the Atlantic Partnership for Tomorrow's Health (PATH) cohort study. Healthy controls were matched to prostate cancer cases (3:1 ratio) on sex, age, smoking status, and the province of residence. Metallome profiles and proportions of arsenic species were measured in toenail and urine samples. Analysis of covariance (ANCOVA) was used to compare the mean percent monomethylarsonic acid (%MMA), dimethylarsonic acid (%DMA), inorganic arsenic (%iAs), primary methylation index (PMI, MMA/iAs), and secondary methylation index (SMI, DMA/MMA). Multivariate analysis of covariance (MANCOVA) was used to compare selected metal concentrations. Mean %MMA was significantly lower and SMI was significantly higher in toenails from prostate cancer cases compared to controls in unadjusted and adjusted models. Proportions of arsenic species were correlated with total arsenic in toenails. Arsenic speciation in urine was not different between cases and controls, nor were metallome profiles in toenails and urine. Our results indicate that toenails are a viable biomarker for altered arsenic speciation in prostate cancer cases and may have greater utility than urine in this context.